Reforming Bureaucracy Through Ethics: Strengthening Institutions for Sustainable Development - Aan Warul Ulum (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study explores the role of public ethics in supporting bureaucratic reform within the Social Service Office of Pasuruan Regency,Indonesia. Grounded in a qualitative case study approach, data were collected through interviews, focus group discussions, and document analysis to uncover how ethical values are internalized and implemented within local governance structures. The findings reveal five critical themes: asymmetrical power dynamics, moral hazard in service delivery, adverse selection in program implementation, institutional governance gaps, and stakeholder exclusion. These issues highlight a disconnect between reformpolicies and daily bureaucratic practices. While ethical codes and reform strategies exist, their enforcement remains inconsistent, often limiting the transformative potential of bureaucratic reform. The study argues that embedding ethics into institutional culture is essential for achieving sustainable, transparent, and inclusive governance, as envisioned in Sustainable Development Goal 16. Recommendations emphasize the need for ethical leadership, participatory governance, and stronger accountability mechanisms. The study concludes that ethical reform is not merely a complementary component of bureaucratic change but a fundamental pillar for building trusted and sustainable public institutions.